Answer:
x=7, x=3
Step-by-step explanation:
[tex]x^{2} -8x+14=2x-7[/tex]
[tex]x^{2} -8x-2x+14+7=0[/tex]
[tex]x^{2} -10x+21=0[/tex]
[tex]\mathrm{For\:a\:quadratic\:equation\:of\:the\:form\:}ax^2+bx+c=0\mathrm{\:the\:solutions\:are\:}[/tex]
[tex]x=[/tex] [tex]\frac{-b\pm \sqrt{b^2-4ac}}{2a}[/tex]
positive
[tex]x=\frac{-\left(-10\right)+\sqrt{\left(-10\right)^2-4\cdot \:1\cdot \:21}}{2\cdot \:1}[/tex]
[tex]x=7[/tex]
negative
[tex]x=\frac{-\left(-10\right)-\sqrt{\left(-10\right)^2-4\cdot \:1\cdot \:21}}{2\cdot \:1}[/tex]
[tex]x=3[/tex]